2021
DOI: 10.21203/rs.3.rs-462937/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Efficacy of Famotidine in improvement of outcomes in Hospitalized COVID-19 Patients: A phase III randomised clinical trial

Abstract: IntroductionAs the first randomized clinical trial, this study evaluated the effect of Famotidine on the improvement of outcomes of hospitalized patients with COVID-19.MethodThis phase III randomized clinical trial was designed with two parallel arms, placebo-controlled, single-blind, and concealed allocation, and recruited 20 patients. Oral Famotidine 160 mg four times a day was given to patients until the discharge day or for a maximum of 14 days. Patients’ temperature, respiration rate, oxygen saturation, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In this study, famotidine caused a reduction in the total WBC count in the BALF. This finding is consistent with a prior study that demonstrated a significant decrease in the WBC count for patients following treatment with famotidine when compared to placebo (Samimagham et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, famotidine caused a reduction in the total WBC count in the BALF. This finding is consistent with a prior study that demonstrated a significant decrease in the WBC count for patients following treatment with famotidine when compared to placebo (Samimagham et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Given the desperate need to develop vaccines as quickly as possible, much effort has been made to develop and manufacture vaccines to prevent the transmission of COVID-19 to healthy individuals (3)(4)(5). Numerous studies have focused on medication therapy and patient recovery; however, vaccination will significantly affect the mortality rate by reducing infection with COVID-19 (3)(4)(5)(6)(7)(8)(9). Nonetheless, like any other compound, vaccines can also cause local and systemic complications (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Numerous studies have focused on medication therapy and patient recovery; however, vaccination will significantly affect the mortality rate by reducing infection with COVID-19 (3)(4)(5)(6)(7)(8)(9). Nonetheless, like any other compound, vaccines can also cause local and systemic complications (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%